مستوى الطموح وعلاقته بدافعية الإنجاز لدى عينة من طلبة قسم علم النفس بجامعة الزاوية (Comprehensive Journal of Science, 2026)
The study aimed to identify the relationship between the level of ambition and achievement motivation among a sample of students from the Department of Psychology at the Faculty of Arts, University of Zawiya. It also sought to examine differences in the level of ambition and achievement motivation according to the study variables (gender, specialization, academic semester, and parents’ educational level). The study sample consisted of 72 male and female students. A descriptive correlational methodology was adopted. To achieve the objectives of the study, the Ambition Level Questionnaire developed by Khadija Al-Ahrash and Fathiya Al-Qasbi (2024) was applied, in addition to the Achievement Motivation Questionnaire developed by the researcher. Using the Statistical Package for the Social Sciences (SPSS), the results revealed a strong, positive, and statistically significant correlation between the level of ambition and achievement motivation among the sample members. The findings also indicated that there were no statistically significant differences in the level of ambition attributable to the variables of gender, academic semester, or parents’ educational level. Moreover, the results showed that the level of achievement motivation was high, with no statistically significant differences in achievement motivation among students due to the variables of gender, academic semester, or parents’ educational level.
Keywords: Ambition, Achievement Motivation, Psychology Students